MEMPELAJARI ARSITEKTUR BATAK TOBA MELALUI KKN-TEMATIK - Manurung, Parmonangan (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
Students of architecture department are required to be able to achieve some scientific competencies determined in graduate learning outcomes (CPL). These various competencies are formulated to achieve student achievements in each course. One of the specified CPLs is knowledge of history and architectural theory. The thematic Community Service Program (called KKN-Tematik) is one of the courses used to help students improve various competencies, both in terms of character, knowledge and skills. One of the KKN-Tematik activities chosen by the Faculty of Architecture and Design, Duta Wacana Christian University in Yogyakarta is Meat village located in Toba Samosir District, , North Sumatera. This study aims to determine the role of the KKN-Tematik Toba Samosir in improving student competence regarding the theory and history of Batak Toba architecture. The results of the study showed an increase in the competency of students by comparing their knowledge of the theory and history of Toba Batak architecture before and after attending this program. It can be concluded that the KKN-Tematik can help students improve their competencies according to the theme of Community Service.